Improved Reaching Law Sliding Mode Control Algorithm Design For DC Motor Based on Kalman Filter - Li Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Aiming at the inaccurately modeling and some uncertain existing in servo system seriously affected the control quality and the instability problem, sliding mode control algorithm with improved reaching law is proposed in this paper. The improved reaching law is used to weaken the chattering problem existing in the sliding mode control. Also the kalman filter is used to inhibit the interference, which make the servo system have strong anti-interference ability and the ability of weakening the chattering problem existing in the sliding mode control. The simulation results show that the algorithm can effectively inhibit the external disturbance and noise existing in the system, and make the system have strong anti-interference ability. At the same time, the chattering also is obviously inhibited, and the method makes the system stability and control quality been further improved.  http://dx.doi.org/10.11591/telkomnika.v12i12.4905